Ecological and economic assessment of the effectiveness of implementing bioenergy technologies in the c onditions of post-war recovery of Ukraine - Dudin, Volodymyr; Дудін, Володимир Юрійович; Polehenka, Marina; Полегенька, Марина Анатоліївна; Tkalich, Olga; Ткаліч, Ольга Вікторівна; Pavlychenko, Artem; Павличенко, А.; Hapich, Hennadii; Гапіч, Геннадій Васильович; Roubik, Hynek; Рубік, Х. (Національний гірничий університет, 2024)
Ecological and economic assessment of the effectiveness of implementing bioenergy technologies for processing organic waste in conditions of technogenic and military risks, while also addressing the need to reduce the extraction of fossil fuels. Methodology. The advanced global experience in bioenergy development is analyzed and considered using modern methods for calculating the technological parameters of biogas plants and determining the economic indicators of their effectiveness. The techno-economic evaluation and justification of the prospects of biogas energy are performed considering the regulatory framework and legislation of Ukraine and the European Union. Findings. With the development of individual biogas plants, the daily output can make approximately: biogas – 370 m3, electricity – 700 kW, thermal energy – 1100 kW. The total value of realized resources per year of operation amounts to €60,370 (of which: electricity – €31,467; thermal energy – €10,907; liquid organic fertilizers – €17,996). With investments of around €270–300 thousand and an annual profit of €21,870, the payback period of investments reaches 12–13 years. Originality. The scientific justification for the prospect and necessity of developing biogas energy in Ukraine has been established to improve overall energy security and the eco-economic efficiency of developing low-waste technologies alongside reducing the extraction of energy resources and greenhouse gas emissions. Assuming the improvement of the regulatory framework for biogas extraction and implementation in line with EU standards, as well as grant funding from various partner countries, the payback period could be reduced from 12 to 5–6 years, which is an acceptable indicator for small private enterprises. Practical value. The practical implementation of the proposed perspectives for the development of Ukraine’s energy sector in the conditions of post-war recovery will reduce dependence on fossil fuels, increase the overall level of environmental and economic efficiency in the energy sector. The possibility of reducing the payback period of capital investments in “green energy” projects by half for farm enterprises has been justified, which positively impacts the environment and energy security of Ukraine. Мета. Еколого-економічна оцінка ефективності впровадження біоенергетичних технологій переробки органічних відходів в умовах техногенних і військових ризиків і необхідності зменшення видобутку викопних корисних копалин. Методика. Проаналізовано та враховано передовий світовий досвід розвитку біоенергетики з використанням сучасних методів розрахунку технологічних параметрів роботи біогазової установки й визначення економічних показників її ефективності. Техніко-економічне оцінювання та обґрунтування перспективності біогазової енергетики виконане з урахуванням нормативно-правової бази й законодавства України та Європейського Союзу. Результати. За умов розвитку індивідуальних біогазових установок добовий вихід може складати близько: біогазу 370 м3 , електроенергії 700 кВт, теплової енергії 1100 кВт. При цьому загальна вартість реалізованих ресурсів за один рік експлуатації становить 60 370 € (з яких: електроенергії – 31 467 €; теплової енергії – 10 907 €; рідких органічних добрив – 17 996 €). При капіталовкладеннях у близько 270–300 тис.€ та щорічного прибутку 21 870 €, термін окупності інвестицій сягає 12–13 років. Наукова новизна. Науково обґрунтована перспективність і необхідність розвитку біогазової енергетики в Україні задля підвищення загального рівня енергетичної безпеки та еколого-економічної ефективності розвитку маловідходних технологій наряду зі зменшенням обсягів видобутку енергетичних корисних копалин і викидів парникових газів. За умови удосконалення нормативноправової бази з видобутку й реалізації біогазової енергії до нормативів ЄС, а також грантового фінансування галузі різними країнами-партнерами, термін окупності може бути скорочений з 12 до 5–6 років, що є прийнятним показником для невеликих приватних підприємств. Практична значимість. Практична реалізація запропонованих перспективних варіантів розвитку енергетичного сектору України в умовах повоєнного відновлення дозволить знизити енергозалежність від викопних корисних копалин, підвищити загальний рівень екологічної та економічної ефективності роботи енергетичного сектору. Обґрунтована можливість зменшення терміну окупності капітальних вкладень у проєктах «зеленої енергетики» вдвічі для умов фермерських господарств, що позитивно впливає на навколишнє середовище та енергетичну безпеку України.
Еколого-економічна оцінка ефективності впровадження біоенергетичних технологій в умовах повоєнного відновлення України
Keywords: biogas plant; біогазова установка; economic efficiency; економічна ефективність; energy security; енергетична безпека; organic waste processing; переробка органічних відходів